2008
DOI: 10.1073/pnas.0800958105
|View full text |Cite
|
Sign up to set email alerts
|

A brain-specific SGK1 splice isoform regulates expression of ASIC1 in neurons

Abstract: Neurodegenerative diseases and noxious stimuli to the brain enhance transcription of serum-and glucocorticoid-induced kinase-1 (SGK1). Here, we report that the SGK1 gene encodes a brain-specific additional isoform, SGK1.1, which exhibits distinct regulation, properties, and functional effects. SGK1.1 decreases expression of the acid-sensing ion channel-1 (ASIC1); thereby, SGK1.1 may limit neuronal injury associated to activation of ASIC1 in ischemia. Given that neurons express at least two splice isoforms, SGK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 34 publications
8
64
0
Order By: Relevance
“…Our results show that GR-responsive isoforms of Sgk1 are confined to astrocytes. The observation that Sgk1-002 is expressed in neurons, but not regulated by morphine or dexamethasone, is consistent with previous data (Arteaga et al, 2008). Although several other transcriptional variants were expressed in neurons and astrocytes, only two of them-Sgk1-003 and Sgk1-001-responded to GR activation, and their induction was restricted to astrocytes.…”
Section: Regulation Of Sgk1 Expression In Neural Cellssupporting
confidence: 92%
See 2 more Smart Citations
“…Our results show that GR-responsive isoforms of Sgk1 are confined to astrocytes. The observation that Sgk1-002 is expressed in neurons, but not regulated by morphine or dexamethasone, is consistent with previous data (Arteaga et al, 2008). Although several other transcriptional variants were expressed in neurons and astrocytes, only two of them-Sgk1-003 and Sgk1-001-responded to GR activation, and their induction was restricted to astrocytes.…”
Section: Regulation Of Sgk1 Expression In Neural Cellssupporting
confidence: 92%
“…In particular, the specific neuronal roles of SGK1 in the CNS stress response (Yuen et al, 2010) and learning and memory (von Hertzen and Giese, 2005) were suggested. Few transcriptional variants of Sgk1 exist (Simon et al, 2007;Arteaga et al, 2008, Fig. 4A), and although one was described as neuron-specific (Sgk1-002; Arteaga et al, 2008), nothing was previously known about transcriptional regulation of Sgk1 in astrocytes.…”
Section: The Effects Of Morphine and Dexamethasonementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study by Arteaga et al (20) reported that SGK1.1, a brain-specific splice isoform of SGK1, decreases expression of ASIC1a at the cell surface. It would be speculative yet interesting to find out whether insulin-mediated ASIC1a regulation occurs through the SGK1.1 signaling pathway in neuronal cells, because SGK1.1 is not regulated by glucocorticoid in the brain (20).…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously reported that a highly conserved alternate transcript of Sgk1, termed Sgk1_v2, encodes NH 2 -terminal variant Sgk1 isoform, Sgk1_i2 (Sgk1.1), that is more stable and increases the activity of a number of cation channels of the ENaC/degenerin family (1,20,27). Although expressed in the CD, this isoform is not regulated by corticosteroids and its relevance in aldosterone-regulated distal nephron Na ϩ transport may be limited.…”
mentioning
confidence: 99%